ANALISIS PENDAPATAN PETERNAK SAPI PERAH LOKAL DAN EKS-IMPOR ANGGOTA KOPERASI WARGA MULYA DI KABUPATEN SLEMAN YOGYAKARTA - Sundari Sundari; Katamso Katamso (Caraka Tani: Journal of Sustainable Agriculture, 2010)
The study was purposed to find out income and feasibility of local and imported dairy cattle farmers member of warga mulya cooperation. This evaluate was done My 15-June 20 2005. The matter used is this evaluate were 27 local dairy cattle farmers and 6 import dairy cattle farmers member of warga mulya in Sleman regency. Using survey method. The result showed that Dairy cattle farmer was profit Rp. 565.394,26/AU/year, while import dairy cattle farmer was lose Rp. 84.585,81/AU/year. RCR for local was 1,11 and import 0,98. Rentability local Dairy cattle farmer = 0,77% and import -1,55%. The conclusion indicated that local Dairy cattle farmer was profit while import Dairy cattle farmer was loosely and the economics analysis of both was unfeasibility.